2009
DOI: 10.1007/s00228-009-0720-x
|View full text |Cite
|
Sign up to set email alerts
|

Statins and total (not LDL) cholesterol concentration and outcome of myocardial infarction: results from a meta-analysis and an observational study

Abstract: Conclusions Total cholesterol measurements can be used with confidence in the absence of LDL measurements to make decisions about statin drug introduction or titration. Randomised trials of statin therapy had good external validity and cholesterol changes and outcomes in trials were comparable to those observed in the setting of usual care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
0
10
1
Order By: Relevance
“…TC decreased by 13% in the statin-unexposed RA group in SP, and this might be because the group included a very small number of patients (n = 18). Compared with results from our previous studies of TC reduction with statin use in the general population (about a 24% reduction) or in PP and SP of statin trials (each 21% reduction, respectively) 15,16 , the reductions of statin-associated TC concentration in patients with OA or RA were smaller, especially in the SP group in OA patients (7%). A lower baseline TC concentration in OA or RA patients than that in the general population appeared to be related to a lesser TC reduction with statin therapy.…”
Section: Rheumatologycontrasting
confidence: 70%
See 1 more Smart Citation
“…TC decreased by 13% in the statin-unexposed RA group in SP, and this might be because the group included a very small number of patients (n = 18). Compared with results from our previous studies of TC reduction with statin use in the general population (about a 24% reduction) or in PP and SP of statin trials (each 21% reduction, respectively) 15,16 , the reductions of statin-associated TC concentration in patients with OA or RA were smaller, especially in the SP group in OA patients (7%). A lower baseline TC concentration in OA or RA patients than that in the general population appeared to be related to a lesser TC reduction with statin therapy.…”
Section: Rheumatologycontrasting
confidence: 70%
“…The Journal of on May 12, 2018 -Published by www.jrheum.org Downloaded from risk 16 . In addition, we have shown that in normal care, TC reductions with lipid-lowering drugs are comparable with reductions seen in the statin trials 17 .…”
Section: Rheumatologymentioning
confidence: 99%
“…In statin trials, we show that TC reductions with lipidlowering drugs is almost as good as LDL-C in predicting outcome [10] and that TC can be used as a reasonable measure of statin efficacy in the absence of LDL-C [11]. In the study presented here, we assessed the effectiveness of statins on TC concentrations and CV events and all-cause mortality in diabetic patients.…”
Section: Introductionmentioning
confidence: 95%
“…However, in the UK, clinicians usually make treatment decisions based on total cholesterol (TC), rather than LDL cholesterol (although the latter can in certain circumstances be calculated), sometimes using high density lipoprotein concentration (HDL-C) measurements as well. We have previously shown that TC reduction with lipid-lowering drugs predicts outcomes in the statin trials almost as well as LDL-C and that TC can be used as a reasonable measure of statin efficacy in the absence of LDL-C [26,27]. We set out to compare the effect of statins on total cholesterol-lowering, CV events, and all-cause mortality in patients with five chronic diseases (COPD, OA, RA, CKD, or DM) using the rest of the population who had no record of having these diseases as the referent group.…”
Section: Introductionmentioning
confidence: 99%